Parasitic infections causing diarrhoea among children less than six years at Al-Nasiriya province - Hussein, Khwam R.; Dahis, Hayat N; Mshhwt, Abdul -Kareem A. (University of Thi-Qar Journal, 2019)
This study aimed to determine the parasitic agents of diarrhoea in children aged less than six years. Out of 780 cases of diarrhea, 206 (26.41 %) had one or more parasitic infections and the remaining 574 (73.58 %) had other enteropathogenic agents of diarrhoea. There were 166 (21.98%) protozoal infections and 40 (5.12 %) helminthes. Male children were 113(45.8 %) and females were 93(44.68 %). The most common pathogens were Giardia lamblia 117 (56.79 %); Entamoeba histolytica 49 (23.78 %); Enterobius vermicularis 27 (13.10 %); Ascaris lumbricoides 9 (4.36 %) and Hymenolepis nana 4 (1.94 %). Moreover, the highest parasitic infections observed during summer months with bottle-feeding nutrition.